سمات الأسرة العربية القوية في قطر، والأردن، وتونس - Doha International Family Institute, (DIFI) (Hamad Bin Khalifa University Press, 2019)
This report focused on studying the Arab family strength and challenges in Qatar, Jordan and Tunisia, and how Arab families use their strengths to overcome the challenges. The report concluded that there are seven important themes in family strength emerged: responsibility, support, good communication, respect, conveying traditions, resilience and love. There are six family challenges identified: societal changes, the need for women empowerment, absence of engaged fathers, financial issues, interference from extended family members and conflict in the family or poor communication. The overall findings from this research can be used by communities and states to help guide and develop educational programs, strategies and initiatives to strengthen and empower families throughout the Arab world.